Computer controlled test system for measuring the parameters of the real thermoelectric module - Ahiska, R.; Dişlitaş, S. (Energy conversion and management, 2011)
Different methods have been developed for measuring the performances of thermoelectric (TE) modules. However, the foundation of these methods accepts the parameters of semiconductors as constant and foresees temperature changes. That is why, the performance calculations of TE modules and their evaluations turn out to be erroneous. The aim of this study was to analyze of the values of the output parameters of operating real TE modules and systems and to be able to make performance analyses. Accordingly, a new computer controlled test system based on the new method founded on easily measurable parameters such as temperature, current and voltage and composed of software and hardware was considered. In this study; algorithms for the determination of the experimental parameters I max, V max and E max and the output parameters Q C , T C , COP, P, Z, K, and R of the TE module were developed and also system hardware and software were realized. The system’s control and interface software was developed by Delphi visual programming language. In order to determine the performance of the developed system, Melcor CP1.0-127-05 model standard TE module was used experimental studies and the superiority of the new method were determined.